Kualitas hidup (yang berhubungan dengan kesehatan mulut) dan stress pada ibu hamil trimester II dengan perkembangan janin: studi korelasi - Debby Yulianthi Maria (Health Sciences and Pharmacy Journal, 2019)
Physiological changes in the body occur during pregnancy, sometimes followed by changes in attitude, state of the soul and behavior. To find out a person's healthy condition, it is necessary to measure the quality of life and stress. This study is to determine the relationship between quality of life related to oral health (OHRQoL) and stress with fetal development in second trimester of pregnant women. This research usedcross sectional approach; populations were pregnant women in second trimester who examined the womb at BPM Endang Purwaningsih Pleret Bantul Yogyakarta there were 56 people in November 2018, using total sampling. The research instrument was the OHIP-14, SRQ-20, and fetal development guidelines. Processing data in this study was using IBM SPSS 20 and Microsoft Excel. The statistical test which is used chi square test. There were 3 respondents with life quality that related to oral health (OHRQoL) in middle category and 53 respondents (94.64%) in the good category quality of life related to oral health (OHRQoL). 41 respondents (73.21%) who were not experiencing stress. There was one respondent with inappropriate fetal development. Chi square test showed that there was no correlation between quality of life related to oral health (0,810 0,05) and stress (0,095 0,05) with fetal development in second trimester of pregnant women in the BPM Endang Purwaningsih Pleret Bantul Yogyakarta. Quality of life related to oral health (OHRQoL) and stress does not affect fetal development in second trimester pregnant women at BPM Endang Purwaningsih Bantul Pleret Yogyakarta.